Foot Exercises in Controlling Blood Sugar Levels in Elderly People with DM at the Baraka Community Health Center, Enrekang Regency, South Sulawesi - Rosdiana, Rosdiana; Rasyid, Djusmadi; Djunaedi, Djunaedi; Noviar, Rizki Andita (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The aging process in the elderly is followed by a decrease in the function of various organs or tissues in the body, including pancreatic beta cells, the effect of which is causing insulin production to decrease, causing blood sugar levels to increase. Diabetes mellitus occurs due to decreased sensitivity to insulin (insulin resistance) or due to a decrease in the amount of insulin produced. To prevent this, one of the pillars of diabetes management is physical exercise or exercise, namely foot exercises. This research method uses a quasi-experimental design with a one group pretest post test design. The aim of this research was to determine the effect of leg exercises on blood sugar levels in elderly people with diabetes mellitus at the Baraka Community Health Center. The sampling technique was carried out using simple random sampling with a sample size of 13 people. The results of the research using the paired t-test showed that the p-value = 0.000 < α = 0.05. This research shows the influence of leg exercises on blood sugar levels in elderly people with diabetes mellitus at the Baraka Community Health Center. The conclusion is that elderly people with diabetes mellitus who carry out foot exercises according to indications and pay attention to contraindications with a frequency of 3 times a week for 30 minutes will have their blood sugar levels under control.